Ultrasound characteristics of a symptomatic and asymptomatic lymphocele after pelvic and/or paraaortic lymphadenectomy - Vit Weinberger; Daniela Fischerova; Ivana Semeradova; Jiri Slama; David Cibula; Michal Zikan (Elsevier, 2019)
Objective: To describe the sonographic characteristics of a lymphocele after pelvic and/or paraaortic lymphadenectomy for gynecological malignancy, analyze and identify ultrasound characteristics related to the symptomatic and asymptomatic lymphoceles. Materials and methods: This is a retrospective analysis of ultrasound examination data collected consecutively in patients after pelvic and/or paraaortic lymphadenectomy in one institution. We recorded the number of lymphoceles, localization, size; ultrasound morphology following International Ovarian Tumor Analysis group classification and symptoms. Results: We described and analyzed 227 lymphoceles (150 asymptomatic and 77 symptomatic) in 161 patients. The asymptomatic lymphocele is typically a thick-walled cystic lesion without vascularization, round and unilocular with anechoic or ground-glass content. The symptomatic lymphocele is typically an oval, or ovoid, unilocular lesion with low-level or anechoic content (ground glass content is unlikely to be present, p < 0.001) and the presence of debris and septations. The lymphocele size (p = 0.001), number of lymphoceles (>1) (p = 0.005), septa (p = 0.002), and debris (p < 0.001) were independent ultrasound features correlating to symptoms development. More than one lymphocele (p = 0.047), septations (p = 0.007) and presence of debris (p < 0.001) were independent ultrasound features correlated to infection. Conclusion: Ultrasound features of symptomatic and asymptomatic lymphocele differ. The clues for lymphocele differential diagnosis are the history of lymphadenectomy and the finding cystic lesion with typically ultrasound features of lymphocele, adjacent to great pelvic vessels. Unique ultrasound features of lymphocele may help to distinguish from tumor relapse, hematoma, abscess, seroma or urinoma. Keywords: Diagnosis, Gynecologic neoplasms, Lymphadenectomy, Lymphocele, Ultrasonography